Is it possible to defeat right-wing populist authorities by winning elections? The erosion of democracy and the system of the triple-masters class in Poland - Żuk, Piotr; Pacześniak, Anna (Frontiers in Political Science, 2022)
The article poses an extremely important question of whether it is possible to remove authoritarian authorities using the methods of parliamentary democracy in a situation where the government has weakened or dismantled democratic mechanisms and institutions. The article treats the rule of right-wing populists as a comprehensive ruling system of the triple-masters class (identified with the apparatus of the ruling party), who fully controls the political, cultural, and economic spheres. The nationalist cultural and ideological superstructure legitimizes the rule of right-wing populists, but it is only a means to build the economic hegemony of the triple-masters class and strengthen their political power. Based on the material gathered during focus group interviews with opposition party activists, the article outlines the main problems faced by the opposition in the state of the triple-masters class.